Genome-wide analysis of the HSP101/CLPB gene family for heat tolerance in hexaploid wheat - Erdayani, Eva (Sci Rep, 2020)
Heat Shock Protein 101 (HSP101), the homolog of Caseinolytic Protease B (CLPB) proteins, has functional conservation across species to play roles in heat acclimation and plant development. In wheat, several TaHSP101/CLPB genes were identified, but have not been comprehensively characterized. Given the complexity of a polyploid genome with its phenomena of homoeologous expression bias, detailed analysis on the whole TaCLPB family members is important to understand the genetic basis of heat tolerance in hexaploid wheat. In this study, a genome-wide analysis revealed thirteen members of TaCLPB gene family and their expression patterns in various tissues, developmental stages, and stress conditions. Detailed characterization of TaCLPB gene and protein structures suggested potential variations of the sub-cellular localization and their functional regulations. We revealed homoeologous specific variations among TaCLPB gene copies that have not been reported earlier. A study of the Chromosome 1 TaCLPB in four wheat genotypes demonstrated unique patterns of the homoeologous gene expression under moderate and extreme heat treatments. The results give insight into the strategies to improve heat tolerance by targeting one or some of the TaCLPB genes in wheat.